ANALISA POMPA COOLING WATER SUPPLY UNTUK MENGHASILKAN STANDAR POMPA YANG EFISIEN DI COOLING TOWER 4 PT EFG - Purwoko, Yohanes Agung; Ridho Febrianto, Fendi; Susilo, Ade; Febriyanto, Rusdi (LPPM Politeknik Astra, 2024)
PT EFG Casting Plant is a manufacturing company that produces engine components used for Daihatsu car engines and some Toyota car engines. The production process is closely related to the high-temperature molding process using a casting machine. Overall, it is cooled using water from a cooling tower and the water is supplied using 2 pumps. An analysis was carried out which aims to determine the efficiency of the two cooling water supply pumps and from the results of this analysis obtained a low efficiency of 66% for each pump, this is because there is a 50% closure of the valve after the cooling water supply pump and if the valve is not done closing can cause cavitation in the pump. The low efficiency of the pump motor can result in less than optimal use of electric power in the pump. To overcome this problem the authors make improvements by providing standard pumps that have optimal efficiency in piping installations at PT EFG. So that from the results of these calculations it was found that initially using two cooling water supply pumps to meet the needs of cooling water, it can be reduced and replaced by using one efficient pump and power use can be optimized. Pump motor efficiency can increase up to 74% and can reduce the use of electric power by 53,049.9 kWh. Keywords: cooling tower, pump efficiency, pump standardization, energy.